A Note on the Automorphism Group of the Bielawski-Pidstrygach Quiver - Mencattini, I.; Tacchella, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
We show that there exists a morphism between a group Γalg introduced by G. Wilson and a quotient of the group of tame symplectic automorphisms of the path algebra of a quiver introduced by Bielawski and Pidstrygach. The latter is known to act transitively on the phase space Cn,₂ of the Gibbons-Hermsen integrable system of rank 2, and we prove that the subgroup generated by the image of Γalg together with a particular tame symplectic automorphism has the property that, for every pair of points of the regular and semisimple locus of Cn,₂, the subgroup contains an element sending the first point to the second.